2004
DOI: 10.1353/eca.2004.0010
|View full text |Cite
|
Sign up to set email alerts
|

Demography and the Long-Run Predictability of the Stock Market

Abstract: This paper was begun during a visit at the Cowles Foundation in Fall 2000 and revised during a visit in Fall 2002: Michael Magill and Martine Quinzii are grateful for the stimulating environment and the research support provided by the Cowles Foundation. We are also grateful to Bob Shiller for helpful discussions, and to participants at the Cowles Conference on Incomplete Markets at Yale University, the SITE Workshop at Stanford University, the Incomplete Markets Workshop at SUNY Stony Brook during the summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
140
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 46 publications
7
140
3
3
Order By: Relevance
“…Those correlates are: labor productivity growth (confirms results with TFP); the change of the U.S. and world dependency ratios and the level and difference of U.S. and world values of Geanakoplos's (2004) MY ratio (confirm results with the level and change of middle age ratios); Federal deficit/GDP and world debt/GDP (confirm results with Federal primary deficit/GDP and US debt/GDP).…”
Section: Datasupporting
confidence: 67%
See 2 more Smart Citations
“…Those correlates are: labor productivity growth (confirms results with TFP); the change of the U.S. and world dependency ratios and the level and difference of U.S. and world values of Geanakoplos's (2004) MY ratio (confirm results with the level and change of middle age ratios); Federal deficit/GDP and world debt/GDP (confirm results with Federal primary deficit/GDP and US debt/GDP).…”
Section: Datasupporting
confidence: 67%
“…26 of these have expected sign, and most though not all are significant. In terms of support for demographic variables as correlates of real rates, these results fall roughly midway between the regression results of Poterba (2001) on the one hand, who finds modest support for demographic variables, and Geanakoplos et al (2004) and Favero et al (2016) on the other, who find exceptionally strong support. Table 3 and line (5c) of Table 4 reflect long periods when the two moved in opposite directions: the mid-1900's-mid 1920 's, 1930-1970, and the mid-1980's-2016. Note that the trend value of this correlate moves quite slowly.…”
Section: Aggregate Savings and Investmentsupporting
confidence: 51%
See 1 more Smart Citation
“…Several studies have also empirically tested the validity of this proposition, yet the results are very mixed. Bakshi and Chen (1994) and Geanakopolos et al (2004) have found evidence of a negative relationship between age structure and stock market returns in the case of the United States. Looking at U.S. data as well, Poterba (2001Poterba ( , 2004 on the other hand could not find any strong econometric evidence that asset returns react to demographic variables.…”
Section: Financial Marketsmentioning
confidence: 99%
“…Relative to this literature, the main novel aspect in our work is to explicitly model differential asset returns. We thereby relate to a literature on aging and the equity premium (Bakshi and Chen 1994;Brooks 2004;Börsch-Supan, Ludwig, and Sommer 2003;Geanakoplos, Magill, and Quinzii 2004;Kuhle 2008) which has not reached a consensus on the quantitative effects of demographic change on differential asset returns. While Brooks (2004) reports substantial increases in the equity premium, the approximate calculations in Börsch-Supan, Ludwig, and Sommer (2003) rather suggest a small increase.…”
mentioning
confidence: 99%